UPAYA GURU DALAM MENANAMKAN NILAI-NILAI AKHLAKUL KARIMAH PADA SISWA MADRASAH IBTIDA’IYAH AL-MUKMININ KALANGSEMANDING PERAK JOMBANG - A. Syafi' AS.; Muh. Akmalul Ubbad (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
This research aims to determine teachers' efforts in instilling moral values in students in the Madrasah Ibtida'iyah Al-Mukminin Kalangsemanding Perak Jombang environment. This research is descriptive qualitative research, namely research that collects data by direct observation and interviews to obtain research data. Meanwhile, data analysis uses three Miles and Huberman style flows, namely data reduction, data presentation and conclusion drawing. The results of the research show that the Akhlakul Karimah Students of Madrasah Ibtida'iyah Al-Mukminin Kalangsemanding Perak Jombang are good. This also shows that the teacher's efforts to instill Akhlakul Karimah values in Madrasah Ibtida'iyah Al-Mukminin Kalangsemanding Perak Jombang students are successful. Although there are still some students who are not used to good morals, such as littering, bullying their peers and liking to say dirty things, they are very small compared to those who already have good morals.